Development of Innovation “tokotki.id” to Increase the Capacity of Household Financial Improvement Strategy of Indonesian Migrant Community in Malaysia - Yuli Agustina; Ita Prihartining Wilujeng; Afwan Hariri Prohimi (Transpublika Publisher, 2024)
tokotki.id is an innovation aimed at enhancing the financial improvement strategies of Indonesian migrant households in Malaysia. The platform offers various services and products specifically designed to meet the needs of the Indonesian community seeking Malaysian products through the currently popular